Poverty of economics : India & the poverty dilemma - Sinha, Krishna Kishore, 1934- (New Delhi : Manak Publications, 2006)
Study with special reference to Bihar, India
Includes bibliographical references and index
Keywords: Poverty -- India -- Bihar